Dehydration process in 1D ammonium lead halide and mixing of organic cations in hybrid perovskites through mechanosynthesis. (25th November 2020) - Prisinzano, Laura; Delmonte, Davide; Ravaglia, Kevin Carlo; Vit, Valentina; Righi, Lara
Abstract: Organic-lead halide perovskites have attracted much attention as a promising material for optoelectronic and photovoltaic applications. However, the broad commercial use of such materials is hindered by their chemical instability. The detrimental processes of degradation often involve the occurrence of hydrated compounds. However, the knowledge of some aspects related to the thermal stability of hydrated lead halides compounds is still very limited. In this work, we report the structural study dealing with the formation of NH4 PbI3 obtained by removing crystallization water from NH4 PbI3  (H2 O)2 with thermal treatment. The hydrated compound is prepared by solvent-free grinding applied on a mixture of NH4 I and PbI2 powders. Upon heating, the structural evolution of the de-hydration process, monitored by powder x-ray diffraction, consists in the rearrangement of the 1D chains of octahedral PbI6 units throughout rotations around a specific crystallographic axis. Besides, the fabrication of the solid solution (CH3 NH3 )1-x (NH4 )x PbI3 with x = 0, 0.05, 0.10, 0.20 is attempted with different conditions of mechanosynthesis. The experimental results confirmed the limited solubility of the NH4 + group in the methylammonium lead iodate perovskite with a maximal substitution limit of 5%.